A systematic review of interventions to prevent lower limb soft tissue running injuries - Yeung, E. W.; Yeung, S. S. (British Journal of Sports Medicine, 2001)
OBJECTIVES:To assess the available evidence for preventive strategies for lower limb soft tissue injuries caused by running. METHODS:An electronic database search was conducted using The Cochrane Musculoskeletal Injuries Group Specialised Register, The Cochrane Controlled Trials Register, Medline, Embase, Sport Discus, Heracles, Atlantes, Biosis, Cinahl, Scisearch, Current Contents, Index To Theses and Dissertation Abstracts. Any randomised or quasi-randomised trials evaluating interventions to prevent running injuries to lower limb soft tissue were included. The eligibility of trials for inclusion and the quality of the trials were independently assessed by two reviewers. RESULTS:Exposure to a high training load (duration, frequency, or running distance) increases the risk of injury, and thus modification of the training schedule can reduce the incidence of injury. The effectiveness of stretching exercises and of insoles in the prevention of lower extremity soft tissue injuries caused by running is not known. Wearing a knee brace with a patellar support ring may be effective in the prevention of anterior knee pain caused by running. CONCLUSIONS:This review provides evidence for the effectiveness of the modification of training schedules in reducing lower limb soft tissue running injuries. More studies are required to quantify the optimal training loads and to confirm that knee braces can prevent knee pain. It is important to note that the studies included in this review had few female participants therefore the results may not be generalisable.